ECOTECT analysis: integration of architectural studio project with theory classroom assignment through computer simulation - Sanusi, Aliyah Nur Zafirah; Denan, Zuraini; Hj Mohd Ariffin, Noor Aziah (2013)
This study analysed the feasibility of introducing environmental analysis software called ECOTECT to 1st and final year Part 1 Architecture students in the International Islamic University Malaysia (IIUM). The study evaluates the students’ response and perception towards the software after completing the environmental analysis assignment, as well as impact to their design skill performances. The nature of ECOTECT assignment differs between the two levels of study. In the final year course, it is an individual assignment and was given during the Environmental Conscious Design (ECD) course, which runs concurrently with the studio design project. For the purpose of integrating the ECD course assignment with the studio design project, the students were required to conduct environmental analysis of their building design using the ECOTECT software. Meanwhile, in the 1st year course, students were given assignment in groups as part of the Environmental Science System (ESS) course. They were required to analyse an existing bungalow which they had chosen as a precedent study to their studio design project. Student feedback surveys on the ECOTECT assignment was conducted among 96 students. The feedbacks obtained from the students are rather positive. In overall, 100% of the final year students and 80% of the 1st year students were fully satisfied with the assignment. In total, 90% of the students had recommended for the assignment to remain within both the ESS and ECD courses. The high percentage of positive students’ feedbacks had shown that the ECOTECT assignment managed to make the learning experience interesting and effective.